Effectiveness of structured health education program on knowledge regarding forensic nursing among B.Sc. (Hons.) Nursing third- and fourth-year students of the College of Nursing, AIIMS Raipur - Prem Chander; Binu Mathew; Priyanka Choudhary; Rekha; Priyanka Choudhary; Ritu Majumdar; Roji Mandal; Rupal Yadav (Journal of Family Medicine and Primary Care)
Background: Forensic nursing is a nursing specialty and sub-specialties that focus on nursing practice who care for victims and offenders, living and deceased at the clinical legal interface. Aims: The aim of the article is to assess the effectiveness of health education on knowledge regarding forensic nursing among B.Sc. (Hons.) Nursing third- and fourth-year students of the College of Nursing, AIIMS Raipur. Settings and Design: The study was conducted at the College of Nursing, AIIMS Raipur. Methods and Material: Pre-experimental one-group pretest and posttest design without the control group was adopted. The sample size was 100 and selected using nonprobability convenience sampling technique. The data were collected by self-structured questionnaire through offline mode to assess the knowledge about forensic nursing. At the end of pretest, structured health education program was given, after seven days posttest was conducted. Statistical Analysis Used: Data were collected and analyzed by using both descriptive and inferential statistics. Results: In pretest, 72% students had poor knowledge and 28% had good knowledge. In posttest, there was a significant increase, only 21% had good knowledge and 79% had excellent knowledge regarding forensic nursing. The mean score of pretests was 10.18 and the mean score of posttests was 23.15 and the mean improvement was 12.97, the paired t value obtained for knowledge was 31.85 which was found significant at 0.05 level (P < 0.05). Conclusions: Result of the study demonstrated that health education program was effective in improving the knowledge among students regarding forensic nursing. The results concluded that the importance of specific training in forensic nursing and support the need of development of a curricular unit in this area for inclusion in nursing curricula.